Seeing the Invisible and Making Sense of It. Scanning, Networks and Scenario Analysis - Yanuar Nugroho; Ozcan Saritas (Foresight and STI Governance)
In parallel with the increasing complexity and uncertainty of social, technological, economic, environmental, political, and value systems (STEEPV), there is a growing need for a systemic approach in Foresight. This paper proposes a methodological approach to demonstrate how the ideas of systems thinking can be applied in Foresight practice. The methodology is based on the joint use of horizon scanning, network analysis, and scenario methods. Horizon Scanning uncovers emerging issues and identifies future surprises and shocks. Network Analysis is a powerful approach to analyzing both the whole system of relations and parts of the system at the same time and hence it reveals the otherwise hidden structural properties of the systems. Network Analysis data allow for the elaboration of a series of Evolutionary Scenarios that not only are capable of giving a snapshot of a particular future, but also explaining the emerging transformation pathways of events and situations from the present into the future as systemic narratives.